Factors responsible for delay in provision of care to suspected COVID-19 patients presenting in surgical emergency and ways to combat it - Saba Sarfraz ,Muhammad Raheel Raza ,Khizar Aziz ,Muhammad Umar ,Khola Noreen ,Malik Shehryar (Journal of Rawalpindi Medical College, 2020)
Introduction: Health care workers are found to be at three times greater risk of getting infected as compared to the general public. Scientists and doctors all over the world have agreed upon the use of PPE including gloves, masks, head covers, face shields, goggles, and jumpsuits in protection against COVID-19. Materials and Methods: This observational prospective study was conducted in the surgical emergency of Holy Family Hospital, Rawalpindi over a period of 2 months and 21 days. Patients included all those who presented to surgical emergency with suspicion of being positive for COVID-19 and time taken by first-line health care workers in attending them. 157 patients were observed for this purpose and 23 first-line surgeons including general, orthopedic, and neurosurgeons were interviewed regarding their fears and concerns about contracting COVID-19 and infecting their families. Results: It was observed that a surgeon took on an average of 10 minutes (+/-3 minutes) in wearing all the personal protective equipment and a total of 14minutes (+/- 5 minutes) in reaching a patient in the trauma room with symptoms suggestive of COVID-19. This was in contrast to a patient presenting to a trauma room who had no respiratory symptoms or fever, in which case, the patient was seen within 3 minutes (+/- 2 minutes) of presentation to a surgical emergency. Out of 23 surgeons, 15 had reasonably aware of the disease while 7 were knowledgeable up to the mark. 17 surgeons were extremely fearful about contracting the disease and infecting their friends and families. 7 surgeons confessed to avoiding COVID-19 patients and 9 surgeons confessed that they commanded their junior surgeons to see suspected COVID-19 patients in the emergency room. Conclusion: We concluded that delay in attending trauma patients suspected of being positive for COVID-19 was a worrisome problem that needed to be addressed. Numerous local and regional circumstances served as a factor for this delay, most important of which came out to be an inadequate provision of PPE, time consumed in collecting and wearing PPE, fear of the disease, and anxiety provoked due to this fear among surgeons.